Comparative analysis of the factors of price competitiveness of niche eco-products on marketplaces in the United States and the European Union - Sokolenko, Alina (Актуальні питання економічних наук, 2026)
The studyʼs relevance stems from the dynamic development of e-commerce and the growing demand for products that meet the principles of sustainable consumption. The purpose of the articleis to study the factors that shape the price competitiveness of niche ecological goods on the marketplaces of the USA and the European Union, and to substantiate approaches to increasing the effectiveness of pricing strategies for their promotion in the digital trading environment. The research process used methods of system analysis, comparative analysis, generalization and systematization of scientific approaches to pricing in digital trade. An analytical approach was applied to the study of factors in the formation of prices for ecological goods on electronic trading platforms, and a structural comparison was used to determine differences in mechanisms of price competition on the marketplaces of the USA and the EU. Results. Based on data on the features of the functioning of marketplaces as digital channels for the sale of niche eco-products and the results of studying the factors of price formation in the e-commerce environment, it was established that the price competitiveness of such products is formed under the influence of a combination of production costs, logistics costs, algorithmic mechanisms for ranking products on platforms and consumer perception of the environmental value of products. The differences in price competition mechanisms in the US and EU marketplaces are characterized, which are due to differences in regulatory environments, competition intensity, and the role of environmental certification in building trust in the product. The main problems in ensuring the price competitiveness of niche eco-products are identified, including high certification costs, logistics costs, regulatory barriers, and the dependence of product visibility on platform algorithmic mechanisms. Conclusions. The analysis indicates that in US marketplaces, the price competitiveness of eco-products largely depends on the flexibility of pricing strategies and the intensity of competition between sellers, while in EU countries, institutional mechanisms for confirming the environmental quality of products and trust in certification systems play a more important role. Prospects for further research include developing quantitative models to assess the price competitiveness of eco-products in the digital marketplaces, as well as studying the impact of platform algorithms on the formation of pricing strategies and consumer behavior in international e-commerce.